A wafer-level sealed silicon cavity microacoustic platform for radio frequency integration - Jiashuai Xu; Zijun Ren; Fangsheng Qian; Junyan Zheng; Yansong Yang (Microsystems & Nanoengineering)
Abstract This study presents a wafer-level sealed silicon cavity (SSC) microacoustic integration platform to address the limitations in the cavity Silicon-on-Insulator (C-SOI) wafers for the 5G/6G wireless communication system. The proposed SSC platform features an extremely smooth suspended membrane with adjustable thickness, flexible cavity shapes with high density, self-formed acoustic wave confinement steps, stable temperature coefficient of frequency (TCF), and highly integrated compatibility with complementary metal-oxide semiconductor (CMOS). A surface smoothing method based on wet oxidation for SSC wafers is presented, which achieves a root mean square (RMS) roughness on the cavity surface of 1.5 nm for the first time. Based on the presented SSC platform, an Al0.75Sc0.25N sealed cavity bulk acoustic wave resonator (S-BAR) is designed, fabricated, and characterized. The experimental results show that the asymmetric second-order (A2) Lamb mode of S-BAR is enhanced for higher frequency with a maximum piezoelectric coupling coefficient ( $${k}_{t}^{2}$$ k t 2 ) of 9.53%, a maximum quality factor (Q) of 439, and a TCF of −11.44 ppm/K. Different designs’ piezoelectric coupling coefficient distribution is consistent with the theoretical prediction. The proposed smoothing process increases the S-BARs’ quality factor by ~400%. The frequency shift caused by the temperature (absolute value of TCF) is reduced by 62% compared with the traditional Al0.75Sc0.25N thin film bulk acoustic wave resonator (without temperature compensation). The enhanced performances demonstrated the potential of SSC in the next-generation highly integrated RF communication systems.